MARITIME AXIS AS INDONESIA’S NEW ECONOMIC POLICY UNDER PRESIDENT JOKOWI - A Zarkasi; Ahmad Baidawi (Prodi Sosiologi FISIP UPR, 2018)
This paper wants to explain the maritime axis as Indonesia's new economic policy under President Jokowi. As is known, Indonesia is the largest maritime and archipelagic country in the world. Indonesia has more than 13,500 islands and 39 straits that are interconnected with other straits in Asian region.Under these conditions, actually Indonesia is a barometer and even the key to regional stability. The successful implementation of the maritime axis policy will have an impact on the welfare of Indonesian people and make Indonesia a maritime country that is sovereign, advanced, independent, strong, and able to make a positive contribution to regional and world security and peace. The Maritime Axis as a new economic policy under President Jokowi in this framework is realized through the marine economic potential that developed from various sectors, especially the capture fisheries sector, fisheries sector, fisheries processing sector, port service sector, exploration and exploitation of offshore energy resources, especially in the area of the Exclusive Economic Zone (EEZ), coastal forestry, trade, shipping and tourism. The results of this paper indicate that the successful implementation of a maritime axis policy as a new economic policy for Indonesia depends on the foundation of national security and is accompanied by the development of maritime infrastructure.This paper uses a qualitative descriptive approach with data and literature sources related to maritime axis policies.